Restoring the missing context in HRM: Habitus, capital and field in the reproduction of Japanese repatriate careers. (16th January 2020) - McCann, Leo; Monteath, Gareth
Abstract: HRM literature often fails to adequately consider the political‐economic context that can strongly influence HR practices and outcomes. This problem is particularly visible as regards international careers. Notions such as "boundaryless careers" privilege HR and employee agency and neglect the complexity, variety, and importance of social structure in influencing careers and constraining agency. Informed by Bourdieu's theory of practice, this paper explores Japanese HRM through the careers of repatriate managers. Through in‐depth and prolonged narrative inquiry, it documents the powerful "forms of capital" that structure the "salaryman" career field. Although tensions and conflicts existed—notably in relation to gender—traditional "lifetime employment" careers remain powerful, highlighting the continued centrality of capital and habitus in reproducing the Japanese white‐collar career field. We conclude by suggesting alternative ways of conceptualizing, researching, and portraying white‐collar careers within varied employment environments that are always shaped by specific and situated contexts.